A method for preparing a polymer film on the surface of an alkali metal-containing material and use in electrochemical energy storage devices

CN123017916APending Publication Date: 2026-10-30SOUTHEAST UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611082117.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-21
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

对于粉体、颗粒、盐晶体、玻璃表面或电极材料颗粒而言,外部包覆形成的聚合物层常存在界面结合力不足、厚度不均匀、难以覆盖复杂表面以及难以大面积制备等问题

Benefits of technology

[0045](1)本发明利用供体-受体界面电荷共振聚合成膜,能够覆盖 NaCl、含钠/钾/锂离子玻璃、电子受体盐、含碱金属电极材料等多种基底,体现反应普适性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017916A_ABST
    Figure CN123017916A_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing a polymer film on the surface of an alkali metal-containing material and application in an electrochemical energy storage device. The method introduces an electron acceptor molecule to the surface of the alkali metal-containing material to make the two contact. At room temperature or under heating conditions, at least part of the electron acceptor molecules and the donor substrate undergo interface charge transfer to form an electron acceptor anion salt. Unreacted neutral electron acceptor molecules coexist with the electron acceptor anion salt at the interface to form a charge resonance, so that the electron acceptor molecules are induced to undergo self-propagating in-situ polymerization to form an electron acceptor molecule-derived polymer film on the surface of the donor substrate. A substrate material with near-surface alkali metal ion depletion and a polymer-coated composite material are obtained. The electrode material obtained by the method is applied in the electrochemical energy storage device, so that a polymer protective layer is constructed in-situ on the surface of the particle to inhibit electrolyte side reactions, transition metal dissolution and structural degradation at high voltage, and the cycle stability of the electrode is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing a polymer film and its application, and more particularly to a method for preparing a polymer film on the surface of an alkali-containing metal material and its application in electrochemical energy storage devices. Background Technology

[0002] Electron acceptor molecules, such as TCNQ and its fluorinated derivative F4TCNQ, possess low least unoccupied molecular orbital energy levels and strong electron affinity, enabling them to accept electrons from donor materials or interface defect states, forming stable radical anions or anionic salts. For a long time, related research has focused on charge-transfer salts, molecular doping, work function modulation, and organic semiconductor interface modification.

[0003] Existing methods for preparing functional polymer thin films typically rely on pre-synthesized polymers, external initiators, catalysts, oxidants, crosslinking agents, or complex deposition equipment. For powders, particles, salt crystals, glass surfaces, or electrode material particles, the polymer layer formed by external coating often suffers from problems such as insufficient interfacial adhesion, uneven thickness, difficulty in covering complex surfaces, and difficulty in large-area preparation.

[0004] On the other hand, in the field of high-energy-density alkali metal batteries, lithium-containing cathode materials such as LiCoO2 and NCM811 are prone to problems such as electrolyte oxidation and decomposition, transition metal dissolution, lattice oxygen release, and surface structure degradation under high cutoff voltages. Although traditional inorganic coating, element doping, or polymer coating methods can improve interface stability to some extent, they still have drawbacks such as complex processes, insufficient bonding between the interface layer and the particle surface, and difficulty in accurately utilizing the surface chemical properties of the material itself.

[0005] Therefore, it is necessary to develop an in-situ film formation method that can, on the one hand, construct a stable artificial interface layer to improve the cycling stability of the electrode under high voltage conditions, and on the other hand, enable the polymer layer formed by external coating to have strong interfacial bonding, uniform thickness, be able to cover complex surfaces, and be prepared over a large area. Summary of the Invention

[0006] Purpose of the invention: The purpose of this invention is to provide a universal method for preparing polymer films on the surface of alkali-containing metal materials; on the one hand, it can construct a stable artificial interface layer to improve the cycling stability of the electrode under high voltage conditions; on the other hand, it can make the polymer layer formed by external coating have strong interfacial bonding, uniform thickness, can cover complex surfaces, and can be prepared over a large area.

[0007] A second objective of this invention is to provide an application of the interface-modified electrode material obtained by the above method in electrochemical energy storage devices.

[0008] Technical solution: The method for preparing a polymer film on the surface of an alkali-containing metal material according to the present invention includes the following steps:

[0009] (1) Using an alkali metal material as a donor substrate, and an organic molecule with electron acceptor properties that can undergo interfacial charge transfer with the alkali metal material as an electron acceptor molecule, the electron acceptor molecule is introduced into the surface of the donor substrate so that the electron acceptor molecule comes into contact with the donor substrate.

[0010] (2) At room temperature or under heating conditions, at least some electron acceptor molecules undergo interfacial charge transfer with the donor substrate to form an electron acceptor anion salt. Unreacted neutral electron acceptor molecules coexist with the electron acceptor anion salt at the interface, forming charge resonance, which induces the electron acceptor molecules to undergo a self-propagating in-situ polymerization reaction, forming an electron acceptor molecule-derived polymer film on the surface of the donor substrate.

[0011] The alkali metal material is at least one of lithium-containing materials, sodium-containing materials, or potassium-containing materials.

[0012] Wherein, the alkali metal-containing material is an alkali metal salt and / or an alkali metal oxide; the alkali metal salt is selected from at least one of alkali metal halides, sodium tetrafluorotetracyanobenzoquinone dimethyl ether, and sodium tetracyanobenzoquinone dimethyl ether; the alkali metal halide is selected from at least one of NaCl, KCl, LiCl, KI, Li6PS5Cl, and Li6PS5Br.

[0013] The alkali-containing metal oxides are LiCoO2, NCM811, and Li7La3Zr2O. 12 Li 3x La 2 / 3-x One or more of TiO3; wherein, Li 3x La 2 / 3-x In TiO3, x is a stoichiometric parameter used to represent the relative content of lithium and lanthanum in lithium lanthanum titanium oxide, and 0 < x ≤ 1 / 6.

[0014] The electron acceptor molecule is a cyano-containing electron acceptor molecule with a conjugated backbone and / or a halogen-substituted electron acceptor molecule; the cyano-containing electron acceptor molecule with a conjugated backbone is preferably a tetracyano-substituted olefin molecule or its derivative; the conjugated backbone is a quinone structure or an olefin structure, and the olefin double bond is connected to four cyano groups, i.e., a tetracyano-substituted olefin derivative.

[0015] The electron acceptor molecule is selected from at least one of the following structures:

[0016] ;

[0017] wherein, X represents H, F, Cl, Br or I; Y represents H, F, Cl, Br or I; Z represents H, F, Cl, Br or I; W represents H, F, Cl, Br or I.

[0018] wherein, the electron acceptor molecule is at least one selected from organic molecules having a quinone skeleton, tetracyanoethylene (TCNE) or hexaazatriphenylenehexacarbonitrile (HAT-CN);

[0019] The electron acceptor molecule having a quinone skeleton is selected from dicyanobenzoquinone-based molecules and / or tetracyanoquinodimethane derivatives; wherein, the dicyanobenzoquinone-based molecule is preferably 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ).

[0020] The tetracyanoquinodimethane derivative is preferably 7,7,8,8-tetracyanoquinodimethane (TCNQ) and / or a tetrafluorotetracyanoquinodimethane derivative; the tetrafluorotetracyanoquinodimethane derivative is preferably 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane (F4TCNQ);

[0021] wherein, in step (1), the alkali metal-containing material is an alkali metal-containing electrode active material; an interface-modified electrode material is obtained in step (2).

[0022] wherein, the alkali metal-containing electrode active material is selected from at least one of lithium ion battery positive electrode materials, sodium ion battery positive electrode materials, and potassium ion battery positive electrode materials.

[0023] wherein, the lithium ion battery positive electrode material includes lithium cobalt oxide (LiCoO2), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4), lithium nickel cobalt manganese oxide layered oxide (LiNi x Co y Mn z O2), lithium nickel cobalt aluminum oxide layered oxide (LiNi x Co y Al z O2), lithium manganate (LiMn2O4), lithium iron phosphate (LiFePO4), lithium-rich manganese-based layered oxide (LRM), one or more thereof; wherein, x, y, z are greater than 0 and x+y+z=1, the lithium-rich manganese-based layered oxide includes materials with the general formula of aLi2MnO3·(1-a)LiMO2, where 0<a<1, M is one or more selected from Ni, Co, Mn, Fe, Al, Mg, Ti, and Zr.

[0024] The sodium-ion battery cathode material is selected from at least one of sodium layered transition metal oxides, Prussian blue compounds, sodium transition metal phosphates, sodium vanadium phosphates, or composite materials thereof.

[0025] The molar ratio of the electron acceptor molecule to the alkali metal electrode active material is 1:10-1:5000; the alkali metal electrode active material and the electron acceptor molecule are mixed and then heat-treated in an inert atmosphere to obtain an interface-modified electrode material; the heat treatment temperature is 100-350 ℃ and the holding time is 0.1-10 h.

[0026] The alkali metal electrode active material and electron acceptor molecules are mixed in a solid phase and then heat-treated in an inert atmosphere; the inert atmosphere includes one or more of argon, nitrogen, and helium; the heat treatment temperature is 100 ℃ to 350 ℃, preferably 180 ℃ to 280 ℃; the holding time is 0.1 h to 10 h, preferably 0.5 h to 3 h.

[0027] In step (1), the alkali-containing metal material is alkali-containing metal glass and / or alkali-containing metal ceramic; in step (2), modified alkali-containing metal glass and / or alkali-containing metal ceramic are obtained after electrons are removed, and a polymer film is located on the surface of the modified alkali-containing metal glass and / or alkali-containing metal ceramic.

[0028] The alkali-containing metal glass is preferably soda-lime glass, sodium silicate glass, lithium silicate glass, or potassium silicate glass.

[0029] In step (1), the method of introducing electron acceptor molecules includes one or more of the following: vapor deposition, sublimation deposition, chemical vapor deposition, physical vapor deposition, vacuum evaporation, atmospheric pressure vapor contact, solid-phase grinding, ball milling, mechanical mixing, solution immersion, spin coating, spraying, or scraping.

[0030] The in-situ polymerization reaction described in step (2) includes one or more of the following: cyano ring trimerization reaction, free radical coupling reaction, conjugate coupling reaction, thermally induced polymerization reaction, charge transfer induced polymerization reaction, or charge resonance induced polymerization reaction.

[0031] In step (2), the polymer film formed during the in-situ polymerization reaction includes a triazine ring structure, a residual cyano structure, a halogen-substituted aromatic structure, a conjugated carbon-nitrogen skeleton, or a combination thereof.

[0032] In step (2), after the polymer film is formed, unreacted electron acceptor molecules and / or surface electron acceptor anion salts are removed by one or more of the following methods: solvent washing, extraction, sublimation removal, purging or vacuum treatment; the solvent includes ethanol, methanol, isopropanol, acetonitrile, acetone, tetrahydrofuran, water or mixtures thereof, preferably ethanol.

[0033] The thickness of the polymer film is 1 nm to 100 μm, preferably 2 nm to 500 nm, and more preferably 2 nm to 100 nm.

[0034] In step (2), the film-forming process can be carried out in the range of room temperature to 500°C, preferably 30°C to 300°C, and more preferably 100°C to 250°C.

[0035] In step (1), the donor substrate is a large-area planar substrate, a curved substrate, a granular substrate, a porous substrate, or a powder substrate; the polymer film can continuously cover the surface of the donor substrate.

[0036] The polymer membrane material obtained in step (2) is an F4TCNQ-derived polymer (Poly-F4TCNQ), a TCNQ-derived polymer (Poly-TCNQ), or an electron acceptor molecule-derived polymer membrane formed by polymerization of F4TCNQ derivatives, TCNQ derivatives, TCNE, DDQ, HAT-CN, or other electron acceptor molecules capable of forming a neutral-anion mixed valence state interface.

[0037] This invention provides the application of interface-modified electrode materials obtained by the above method in electrochemical energy storage devices.

[0038] The polymer film in the interface-modified electrode material is a polymer interface protective layer used to suppress one or more of the following under high voltage: electrolyte oxidative decomposition, transition metal dissolution, surface phase transition, lattice oxygen release, interface impedance increase, or loss of active alkali metal.

[0039] The electrochemical energy storage device includes lithium-ion batteries, sodium-ion batteries, potassium-ion batteries, hybrid-ion batteries, or solid-state batteries.

[0040] Invention principle:

[0041] The inventors discovered that at the interface between the donor material and the electron acceptor molecule, in addition to the unidirectional charge transfer from donor to acceptor, there are often unreacted neutral electron acceptor molecules and reduced electron acceptor anions present simultaneously. Neutral molecules and anions can form mixed valence pairs or mixed valence interfaces, resulting in intermolecular charge resonance. This type of neutral-anion charge resonance not only alters the electronic structure of the electron acceptor molecule but may also lower the energy barriers for subsequent bonding and polymerization reactions, thereby triggering a self-propagating polymerization film-forming process.

[0042] This invention enables electron acceptor molecules to form continuous polymer films on different donor substrate surfaces through charge transfer, anion salt generation, neutral-anion charge resonance, and self-propagation polymerization. Simultaneously, this reaction mechanism is applied to the surface of alkali metal battery cathode materials to construct a stable artificial interface layer, thereby improving the cycle stability of the electrode under high voltage conditions.

[0043] By utilizing the lithium ions, sodium ions, and their interfacial electronic structure on the surface of alkali metal cathode materials, electron acceptor molecules are induced to polymerize in situ to form a polymer protective layer, thereby suppressing side reactions at the electrode / electrolyte interface and the degradation of the cathode structure under high voltage.

[0044] Beneficial effects: Compared with the prior art, the present invention achieves the following significant effects:

[0045] (1) The present invention utilizes the charge resonance polymerization of the donor-acceptor interface to form a film, which can cover a variety of substrates such as NaCl, sodium / potassium / lithium ion glass, electron acceptor salt, and alkali metal electrode materials, demonstrating the universality of the reaction.

[0046] (2) The film formation is triggered by the substrate’s own electron-donating ability and cation migration / coordination ability. No external traditional initiators, oxidants, catalysts or pre-synthesized polymers are required, and the process is simple.

[0047] (3) The present invention drives polymerization through charge resonance between electron acceptor anionic salt and neutral electron acceptor molecules, so that the polymer film is generated in situ on the substrate surface, which has better adhesion and continuity.

[0048] (4) This invention can be used for the preparation of large-area polymer films on planar substrates, as well as for coating the surface of powder and particulate materials. It is suitable for application in functional films, interface layers and electrode material post-processing.

[0049] (5) In the cathode material of alkali metal batteries, the polymer interface layer formed by the present invention can reduce the direct contact between the electrolyte and the active surface, suppress side reactions and structural degradation under high voltage, and improve cycle stability and interface stability.

[0050] (6) The present invention further demonstrates through comparative examples that the film-forming effect depends on the electron acceptor ability, salt-forming ability, polymerizable structure, and ratio window of the electron acceptor molecule to the substrate. Molecules such as tetrafluoro-1,4-benzoquinone with insufficient electron acceptor ability or subsequent polymerization ability are difficult to form large-area continuous films on sodium-containing glass surfaces; the performance improvement of LiCoO2 modified samples at non-preferred dosages is limited or the interfacial impedance increases. Attached Figure Description

[0051] Figure 1 This is the Raman spectrum of sample Polymer@LiCoO2 in Example 1 of this invention;

[0052] Figure 2 This is the Raman spectrum of sample Polymer@NCM811 in Example 3 of this invention;

[0053] Figure 3 This is the Polymer@Li sample in Example 5 of the present invention. 1.2 Ni 0.25 Mn 0.75 Raman spectrum of O2;

[0054] Figure 4 This is the Raman spectrum of sample Polymer@LiMn2O4 in Example 6 of this invention;

[0055] Figure 5 This is a scanning electron microscope image of the sample Polymer@LiCoO2 in Example 1 of this invention;

[0056] Figure 6 is an optical photograph of the sample of F4TCNQ polymerized in situ on the surface of NaCl in Example 7 of the present invention, wherein (a) the initial NaCl crystal, (b) NaCl exposed to F4TCNQ vapor, and (c) NaCl coated with polymer film.

[0057] Figure 7 is an optical photograph of the F4TCNQ in situ polymerized film on a sodium-containing glass surface in Example 9 of the present invention;

[0058] Figure 8 is a scanning electron microscope image of the film formed by in-situ polymerization of F4TCNQ on the NaCl surface in Example 7 of the present invention;

[0059] Figure 9 This is a scanning electron microscope image of the F4TCNQ in situ polymerized film on a sodium-containing glass surface in Example 9 of this invention;

[0060] Figure 10 shows the Raman spectra of samples from Examples 8 and 9 of this invention;

[0061] Figure 11 shows the cycle performance of the samples from Examples 1, 2, and 1 of the present invention as positive electrode materials for lithium-ion batteries.

[0062] Figure 12 shows the cycle performance of the samples from Examples 3, 4, and Comparative Example 2 of this invention as positive electrode materials for lithium-ion batteries.

[0063] Figure 13 shows the cycle performance of the samples from Example 5 and Comparative Example 3 of this invention as positive electrode materials for lithium-ion batteries. Detailed Implementation

[0064] The present invention will now be described in further detail.

[0065] Example 1

[0066] Construction of the F4TCNQ-induced in-situ polymerization interface layer on the LiCoO2 surface:

[0067] Commercial LiCoO2 powder was used as the lithium-containing cathode material, and F4TCNQ powder was used as the electron acceptor molecule. The powder was prepared according to a F4TCNQ:LiCoO2 molar ratio of 1:200. The two materials were thoroughly mixed for 30 min using mechanical grinding, ball milling, or drum mixing. The mixed powder was transferred to a quartz boat and heat-treated under a nitrogen inert atmosphere at 250 ℃ for 1 h. After heat treatment, the powder was washed three times with anhydrous ethanol to remove unreacted F4TCNQ and soluble lithium salt byproducts; subsequently, it was vacuum dried at 100 ℃ to obtain a polymer interface-modified Polymer@LiCoO2 composite material. The Polymer@LiCoO2 composite material was thoroughly mixed with Super P and PVDF at a mass ratio of 90:5:5 to form an electrode slurry, which was then coated onto aluminum foil to obtain a battery electrode sheet. The performance of this electrode sheet was tested. Cyclic testing was conducted at a 1 C rate within a voltage range of 3.0–4.6 V.

[0068] Example 2

[0069] F4TCNQ-induced in-situ polymerization interface layer construction on LiCoO2 surface:

[0070] Commercial LiCoO2 powder was used as the lithium-containing cathode material, and F4TCNQ powder was used as the electron acceptor molecule. The powder was prepared according to a F4TCNQ:LiCoO2 molar ratio of 1:500. The two materials were thoroughly mixed for 30 min using mechanical grinding, ball milling, or drum mixing. The mixed powder was transferred to a quartz boat and heat-treated under a nitrogen inert atmosphere at 250℃ for 1 h. After heat treatment, the powder was washed three times with anhydrous ethanol to remove unreacted F4TCNQ and soluble lithium salt byproducts; subsequently, it was vacuum dried at 100℃ to obtain a polymer interface-modified Polymer@LiCoO2 composite material. The Polymer@LiCoO2 composite material was thoroughly mixed with Super P and PVDF at a mass ratio of 90:5:5 to form an electrode slurry, which was then coated onto aluminum foil to obtain a battery electrode sheet. The performance of this electrode sheet was tested. Cyclic testing was conducted at a 1 C rate within a voltage range of 3.0–4.6 V.

[0071] Example 3

[0072] Construction of the F4TCNQ-induced in-situ polymerization interface layer on the surface of NCM811:

[0073] Commercial NCM811 powder was used as the lithium-containing cathode material, and F4TCNQ powder was used as the electron acceptor molecule. The powder was prepared according to a F4TCNQ:NCM811 molar ratio of 1:200. The two materials were thoroughly mixed for 30 min using mechanical grinding, ball milling, or drum mixing. The mixed powder was transferred to a quartz boat and heat-treated under a nitrogen inert atmosphere at 250℃ for 2 h. After heat treatment, the powder was washed three times with anhydrous ethanol to remove unreacted F4TCNQ and soluble lithium salt byproducts; subsequently, it was vacuum dried at 100℃ to obtain a polymer interface-modified Polymer@NCM811 composite material. The Polymer@NCM811 composite material was thoroughly mixed with Super P and PVDF at a mass ratio of 90:5:5 to form an electrode slurry, which was then coated onto aluminum foil to obtain a battery electrode sheet. The performance of this electrode sheet was tested. Cyclic testing was conducted at a 1C rate within a voltage range of 3.0-4.5V.

[0074] Example 4

[0075] Construction of the F4TCNQ-induced in-situ polymerization interface layer on the surface of NCM811:

[0076] Commercial NCM811 powder was used as the lithium-containing cathode material, and F4TCNQ powder was used as the electron acceptor molecule. The powder was prepared according to a F4TCNQ:NCM811 molar ratio of 1:20. The two materials were thoroughly mixed for 30 min using mechanical grinding, ball milling, or drum mixing. The mixed powder was transferred to a quartz boat and heat-treated under a nitrogen inert atmosphere at 250℃ for 2 h. After heat treatment, the powder was washed three times with anhydrous ethanol to remove unreacted F4TCNQ and soluble lithium salt byproducts; subsequently, it was vacuum dried at 100℃ to obtain a polymer interface-modified Polymer@NCM811 composite material. The Polymer@NCM811 composite material was thoroughly mixed with Super P and PVDF at a mass ratio of 90:5:5 to form an electrode slurry, which was then coated onto aluminum foil to obtain a battery electrode sheet. The performance of this electrode sheet was tested. Cyclic testing was conducted at a 1 C rate within a voltage range of 3.0-4.5V.

[0077] Example 5

[0078] F4TCNQ induces Li 1.2 Ni 0.25 Mn 0.75 Construction of the O2 surface in-situ polymerization interface layer:

[0079] Take commercial Li 1.2 Ni 0.25 Mn 0.75 O2 powder was used as the lithium-containing cathode material, and F4TCNQ powder was used as the electron acceptor molecule. According to the F4TCNQ:Li... 1.2 Ni 0.25 Mn 0.75 The O2 molar ratio was 1:200. The two were thoroughly mixed for 30 minutes using mechanical grinding, ball milling, or drum mixing. The mixed powder was transferred to a quartz boat and heat-treated under a nitrogen inert atmosphere at 250℃ for 2 hours. After heat treatment, the powder was washed three times with anhydrous ethanol to remove unreacted F4TCNQ and soluble lithium salt byproducts; subsequently, it was vacuum-dried at 100℃ to obtain the polymer interface layer modified Polymer@Li 1.2 Ni 0.25 Mn 0.75 O2 composite material. Polymer@Li 1.2 Ni 0.25 Mn 0.75O2 composite material was thoroughly mixed with SuperP and PVDF at a mass ratio of 90:5:5 to form an electrode slurry, which was then coated onto aluminum foil to obtain a battery electrode sheet. The performance of the electrode sheet was then tested. Cyclic testing was conducted at a 1 C rate within a voltage range of 3.0-4.5V.

[0080] Example 6

[0081] Construction of the F4TCNQ-induced in-situ polymerization interface layer on the LiMn2O4 surface:

[0082] Commercial LiMn2O4 powder was used as the lithium-containing cathode material, and F4TCNQ powder was used as the electron acceptor molecule. The powder was prepared according to a molar ratio of F4TCNQ:LiMn2O4 of 1:200. The two materials were thoroughly mixed for 30 min using mechanical grinding, ball milling, or drum mixing. The mixed powder was transferred to a quartz boat and heat-treated under a nitrogen inert atmosphere at 250℃ for 2 h. After heat treatment, the powder was washed three times with anhydrous ethanol to remove unreacted F4TCNQ and soluble lithium salt byproducts; subsequently, it was vacuum dried at 100℃ to obtain a polymer interface-modified Polymer@LiMn2O4 composite material.

[0083] Example 7

[0084] In-situ polymerization of F4TCNQ on NaCl surface to form a film:

[0085] NaCl crystals were used as the donor substrate and placed in a reaction vessel; F4TCNQ powder was used as the electron acceptor molecular source. The system was heated to 250°C under an inert atmosphere, low vacuum, or controlled atmosphere, allowing F4TCNQ vapor to contact the NaCl surface for 30 min. F4TCNQ accepted electrons on the NaCl surface and formed F4TCNQ anions, while NaCl... + The NaF4TCNQ salt layer is formed through pairing. Subsequently, the continuously arriving neutral F4TCNQ forms a mixed valence environment with the interfacial NaF4TCNQ, inducing F4TCNQ polymerization to form a continuous Poly-F4TCNQ film. After the reaction, the NaF4TCNQ salt layer can be selectively removed by washing with ethanol, leaving the polymer film covering the NaCl surface.

[0086] Example 8

[0087] In-situ polymerization of F4TCNQ onto the surface of lithium niobate (LiNbO3) to form a film:

[0088] LiNbO3 crystals were used as the donor substrate and placed in a reaction vessel; F4TCNQ powder was used as the electron acceptor molecular source. The system was heated to 250°C under an inert atmosphere, low vacuum, or controlled atmosphere, allowing F4TCNQ vapor to contact the LiNbO3 surface for 30 min.

[0089] Example 9

[0090] Preparation of large-area polymer films using F4TCNQ on sodium-containing glass surfaces:

[0091] A sodium silicate glass slide, 10 cm × 10 cm in size and 1 cm thick, was used as the donor substrate. After cleaning and drying, the glass substrate was placed together with F4TCNQ powder in the reaction chamber. The system was heated to 250 °C and treated for 30 min.

[0092] In this process, F4TCNQ can accept electrons from near-surface defect states or electron-donating sites in the glass, and the Na in the glass... + The salt migrates to the surface and pairs with F4TCNQ anions to form a NaF4TCNQ type surface salt layer. Neutral F4TCNQ further undergoes charge resonance polymerization with the surface anionic salt to obtain a continuous Poly-F4TCNQ film. After washing with ethanol to remove the surface salt crystals, a polymer film tightly adhered to the glass substrate is obtained. This example demonstrates that the method of the present invention is suitable for film formation on large-area planar substrates, and can also be used to remove or partially remove sodium / potassium ions from the surface of tempered glass, control the stress of tempered glass, and obtain cuttable tempered glass.

[0093] Comparative Example 1

[0094] High-voltage cycling comparison of uncoated LiCoO2:

[0095] Commercial LiCoO2 powder was thoroughly mixed with Super P and PVDF at a mass ratio of 90:5:5 to form an electrode slurry. This slurry was then coated onto aluminum foil to obtain a battery electrode sheet, and its performance was tested. Cyclic testing was conducted at a 1 C rate within a voltage range of 3.0-4.6V.

[0096] Comparative Example 2

[0097] High-voltage cycling comparison of uncoated NCM811:

[0098] Commercial NCM811 powder was thoroughly mixed with Super P and PVDF at a mass ratio of 90:5:5 to form an electrode slurry. This slurry was then coated onto aluminum foil to obtain a battery electrode sheet, and its performance was tested. Cyclic testing was conducted at a 1C rate within a voltage range of 3.0-4.5V.

[0099] Comparative Example 3

[0100] Uncovered Li 1.2 Ni 0.25 Mn 0.75 High-voltage cycling comparison of O2:

[0101] Take commercial Li 1.2 Ni 0.25 Mn 0.75 O2 powder, Super P, and PVDF were thoroughly mixed at a mass ratio of 90:5:5 to form an electrode slurry. This slurry was then coated onto aluminum foil to obtain a battery electrode sheet, and its performance was tested. Cyclic testing was conducted at a 1 C rate within a voltage range of 3.0-4.5V.

[0102] Depend on Figure 1-4 As can be seen, the Raman spectra showed characteristic signals of the polymers obtained in Examples 1, 3, 5, and 6, respectively, indicating that the methods in Examples 1, 3, 5, and 6 successfully coated the corresponding polymers onto the LCO surface, NCM811 surface, and Li surface, respectively. 1.2 Ni 0.25 Mn 0.75 O2 surface, LiMn2O4 surface.

[0103] Depend on Figure 5 It can be seen that the LCO coated in Example 1 still retains its original microstructure.

[0104] Depend on Figure 6 It can be seen that the color changes of F4TCNQ before and after reacting with NaCl crystals in Example 7 are significant.

[0105] Depend on Figure 7 It can be seen that the color change of the surface of F4TCNQ before and after the reaction with glass in Example 9 is shown.

[0106] Depend on Figure 8 The microstructure of the polymer film formed by the reaction of F4TCNQ and NaCl crystals in Example 7 can be seen.

[0107] Depend on Figure 9 The microstructure of the polymer film formed by the reaction of F4TCNQ with glass in Example 9 can be seen.

[0108] Depend on Figure 10 It can be seen that the polymers on the lithium niobate crystal surface of Example 8 and the sodium-containing glass surface of Example 9 were successfully generated.

[0109] Depend on Figure 11 It can be seen that the cyclic stability of LCO after coating in Examples 1 and 2 is significantly improved.

[0110] Depend on Figure 12 It can be seen that the cyclic stability of NCM811 after coating in Examples 3 and 4 was significantly improved.

[0111] Depend on Figure 13 It can be seen that the Li coated in Example 5 1.2 Ni 0.25 Mn 0.75 The cyclic stability of O2 was significantly improved.

Claims

1. A method for preparing a polymer film on the surface of an alkali-containing metal material, characterized in that, Includes the following steps: (1) Using an alkali metal material as a donor substrate, and an organic molecule with electron acceptor properties that can undergo interfacial charge transfer with the alkali metal material as an electron acceptor molecule, the electron acceptor molecule is introduced into the surface of the donor substrate so that the electron acceptor molecule comes into contact with the donor substrate. (2) At room temperature or under heating conditions, at least some electron acceptor molecules undergo interfacial charge transfer with the donor substrate to form an electron acceptor anion salt. Unreacted neutral electron acceptor molecules coexist with the electron acceptor anion salt at the interface, forming charge resonance, which induces the electron acceptor molecules to undergo a self-propagating in-situ polymerization reaction, forming an electron acceptor molecule-derived polymer film on the surface of the donor substrate.

2. The method for preparing a polymer film on the surface of an alkali-containing metal material according to claim 1, characterized in that, The alkali metal material is at least one of lithium-containing materials, sodium-containing materials, or potassium-containing materials.

3. The method for preparing a polymer film on the surface of an alkali-containing metal material according to claim 2, characterized in that, The alkali metal-containing material is an alkali metal salt and / or an alkali metal oxide; the alkali metal salt is selected from at least one of alkali metal halides, sodium tetrafluorotetracyanobenzoquinone dimethyl ester, and sodium tetracyanobenzoquinone dimethyl ester; the alkali metal halide is selected from at least one of NaCl, KCl, LiCl, NaBr, and KI.

4. The method for preparing a polymer film on the surface of an alkali-containing metal material according to claim 1, characterized in that, The electron acceptor molecule is a cyano-containing electron acceptor molecule with a conjugated backbone and / or a halogen-substituted electron acceptor molecule; the conjugated backbone is a quinone structure or an olefin structure, and the olefin double bond is connected to four cyano groups.

5. The method for preparing a polymer film on the surface of an alkali-containing metal material according to claim 4, characterized in that, The electron acceptor molecule is selected from at least one of the following structures: ; Where X represents H, F, Cl, Br or I; Y represents H, F, Cl, Br or I; Z represents H, F, Cl, Br or I; and W represents H, F, Cl, Br or I.

6. The method for preparing a polymer film on the surface of an alkali-containing metal material according to claim 5, characterized in that, The electron acceptor molecule is at least one of an organic molecule with a quinone skeleton, tetracyanoethylene (TCNE), or hexaazatriphenylhexanitrile (HAT-CN); the electron acceptor molecule with a quinone skeleton is selected from dicyanobenzoquinone molecules and / or tetracyanobenzoquinone dimethane derivatives; the tetracyanobenzoquinone dimethane derivative is selected from 7,7,8,8-tetracyano-p-benzoquinone dimethane (TCNQ) and / or tetrafluorotetracyanobenzoquinone dimethane derivatives.

7. The method for preparing a polymer film on the surface of an alkali-containing metal material according to claim 1, characterized in that, In step (1), the alkali-containing metal material is an alkali-containing metal electrode active material; in step (2), an interface-modified electrode material is obtained.

8. The method for preparing a polymer film on the surface of an alkali-containing metal material according to claim 1, characterized in that, In step (1), the alkali-containing metal material is alkali-containing metal glass and / or alkali-containing metal ceramic; in step (2), the modified alkali-containing metal glass and / or alkali-containing metal ceramic formed after electron removal is obtained, as well as the polymer film located on the surface of the modified alkali-containing metal glass and / or alkali-containing metal ceramic.

9. The method for preparing a polymer film on the surface of an alkali-containing metal material according to claim 7, characterized in that, The molar ratio of the electron acceptor molecule to the alkali metal electrode active material is 1:10-1:5000; the alkali metal electrode active material and the electron acceptor molecule are mixed and then heat-treated in an inert atmosphere to obtain an interface-modified electrode material; the heat treatment temperature is 100-350 ℃ and the holding time is 0.1-10 h.

10. The application of the interface-modified electrode material obtained by the method of claim 7 in an electrochemical energy storage device.